COUNTER-KNOWLEDGE, CRITICISM, AESTHETICS AND ACADEMIC DISOBEDIENCE: A THEMATIC HISTORY OF THE SOUTH AFRICAN QUALITATIVE METHODS CONFERENCE - Hook, Derek (PINS-Psychology in Society, 2026)
The event of the 2000 "What is critical in critical psychology?" conference marked the sixth birthday of the South African Annual Qualitative Methods Conference (QMC). Beginning as a largely student-run event in the Psychology Department of the University of the Witwatersrand in 1995, the QMC has grown both in scale and stature, resulting in a series of inter-linked conferences (A Spanner in the Works of the Factory of Truth - 1995, The Body Politic - 1996, Touch Me I'm Sick- 1997, Histories of the Present- 1998, Normality & Pathology - 1999, What is critical in Critical Psychology? - 2000). Despite remaining open to contributions from a broad variety of disciplines, the event's foundation has always remained that of psychology. In fact, if a single agenda for the event had to be isolated, it may well be that of attempting to bolster the practice of critical psychology in the South African context. The fourth QMC was something of a milestone in the history of the event Not only did it represent the most multi-disciplinary - and hence diverse - conference of the six to date, it also attained the strongest rapprochement between aesthetic and academic disciplines And as such several of the following examples of key QMC events will stem from this conference. The theme of this event, the genealogical injunction to write a "history of the present•, provides a useful and synthesizing motif through which we may unify and contain many of the priorities of the Qualitative Methods series of conferences Before turning to this thematic however, this paper will provide a brief overview of the practical agendas historically characteristic of the QMC From this will follow a foregrounding of three fundamental concepts prioritized by the QMCs: 1) the enabling of effective criticism, 2) the production of "counter-knowledge•, and 3) the use of aesthetics as means of politics. In this connection, and largely for convenience's sake I will use the work of Michel Foucault as something of an explanatory armature - a stabilizing reference point - through which to elaborate these agendas, although I admit that this may provide more an illusion of cohesion than the "institution" of the QMC itself deserves.